Une approche cognitive du potentiel sémantique et constructionnel du verbe "casser". Une confrontation aux verbes "briser" et "couper" - Bordignon, Frédérique (HAL (Le Centre pour la Communication Scientifique Directe), 2003)
This work deals with the semantic and constructional potential of "casser". It fits into the Cognitive Grammar framework (Langacker, 1987) and ore particularly the Network model that provides two types of categorisation relationship and the concepts of schema and prototype that helps giving account of the various usages of a lexical item. These usages have been identified thanks to a corpus of literary and journalistic texts. Moreover, experiments have been made with French speakers (sentences classification) and french-slovak bilingual speakers in order to better define the semantic of the French verbs "casser" and "briser" and the relationship that unites one with the other. For the description of the constructional potential, "casser" is compared to "couper. They share the same syntactic behaviour as far as abstracts uses of "casser" and all the uses of "couper" are concerned. This phenomenon is described in terms of transitivity and ergativity as they have been described by Davidse (1998)